Emerging Markets (IntechOpen, 2023)
The rapid growth and development of emerging economies offer both opportunities and threats for international businesses. Understanding the economic development of emerging markets, combined with a knowledge of the increasingly complex international business market, enables better exploitation of opportunities in increasingly competitive world markets. The BRIC countries, the most prominent emerging markets, have long been discovered by foreign firms due to their enormous potential for investment opportunities. This book offers a comprehensive look at emerging markets, especially as they integrate with the global economy. It offers a conceptual framework to analyze emerging markets from multiple perspectives, including those of indigenous entrepreneurs struggling to overcome constraints to build world-class businesses, multinationals from developed countries tapping into emerging markets for their next growth spurt, and domestic and foreign investors seeking to profit from investment opportunities in emerging markets.